EDUCATIONAL DYNAMICS ON LEARNING HINDU RELIGIOUS EDUCATION AND ETHICS IN PUBLIC JUNIOR HIGH SCHOOL 1 DENPASAR AND PUBLIC JUNIOR HIGH SCHOOL 2 DENPASAR - Ni Made Sri Uttami Dharmaningsih; I Wayan Winaja; Wayan Paramartha (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
The Covid-19 pandemic has brought major changes to the education sector, shifting the learning process from face-to-face instruction to online and later to limited face-to-face learning (PTMT). These changes demanded significant adaptation by schools, teachers, and students, particularly in maintaining learning quality under challenging conditions. Despite these obstacles, Public Junior High School 1 Denpasar and Public Junior High School 2 Denpasar demonstrated resilience and continued achievement, particularly in Hindu Religious Education and Ethics. This study aims to examine the implications of educational dynamics on the learning of Hindu Religious Education and Ethics in these two schools. Using a qualitative descriptive method, data were collected through observation, in-depth interviews, and documentation. The analysis was grounded in McClelland's motivation theory. The results show that the educational dynamics have influenced three key aspects of student learning: cognitive, affective, and psychomotor. These findings highlight how learning processes in both schools successfully adapted to challenges while still nurturing students’ academic abilities, character, and cultural-spiritual values.